Analytical Validation of Smartphone Spectroscopic Technic Used in an Educational Kinetic Study - S. Raissi; F. Fakhfakh (International Journal of Analytical Chemistry)
Use of smartphone-based spectroscopy is showing a constant growth since last year. It presents the advantage of being widely available for everyone. The most important thing is that it is still a low-cost method adapted to the education context. However, as all analytical methods, it should be validated to ensure the reliability of its results. In this study, we present the steps of the validation process with its statistical tests applied to the dosage of di-iode. Shapiro–Wilk test revealed that our method has a random character. Homogeneity of variance analyses using the Cochran test confirmed the precision of the method. The Fisher test revealed the linearity of the model of correlation between I2 concentration and the response. The relation between response and concentration is A = 1000 C + 0.002. From the parameters of the linear regression of the model, we deduced the limits of quantification and XLq = 4·10−5 mol·L−1 and XLd = 1·10−5 mol·L−1. Thanks to tightness of the sample, the method of I2 dosage was successfully applied in iodine quantification to monitor acetone iodination during time in the context of kinetic studies with minimum system trouble. Being low cost, this method can facilitate access to physical methods in educational laboratories.